2010
DOI: 10.1080/02786826.2010.511320
|View full text |Cite
|
Sign up to set email alerts
|

A High-Temperature Reducing Jet Reactor for Flame-Based Metal Nanoparticle Production

Abstract: We present a new flame-based aerosol reactor configuration that combines thermal decomposition and hydrogen reduction to produce metal nanoparticles. This approach uses a fuel-rich hydrogen flame as a source of low-cost energy to initiate particle synthesis, but separates the flame chemistry from the particle formation chemistry. Hot combustion products pass through a nozzle to produce a high-temperature reducing jet. A liquid precursor solution is rapidly atomized, evaporated, and decomposed by the expanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…Our prototype HTRJ reactor was described in detail by Scharmach et al (2010). It uses oxygen at a flow rate of ∼2.3 standard liters per minute (SLM) and a larger flow of hydrogen and nitrogen (∼14 SLM total) to form an inverted diffusion flame.…”
Section: Materials and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Our prototype HTRJ reactor was described in detail by Scharmach et al (2010). It uses oxygen at a flow rate of ∼2.3 standard liters per minute (SLM) and a larger flow of hydrogen and nitrogen (∼14 SLM total) to form an inverted diffusion flame.…”
Section: Materials and Synthesismentioning
confidence: 99%
“…The advantages of HTRJ technology stem from the use of low-cost, water-soluble nitrate precursors and a low-cost energy source in a continuous and environmentally benign process. The flame-based aerosol reactor configuration used to make these nanostructured coatings was developed by Scharmach et al (2010) and is described further below. The key addition to the previously described system was a holder for mounting a 12.5 mm diameter substrate in the aerosol flow, just above the particle formation chamber, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…6 It consists of a burner in which a relatively small flow of oxygen (2 SLM) and a larger flow of hydrogen and nitrogen (12 SLM total) support an inverted diffusion flame (oxidant on the inside, fuel on the outside) at the tip of the oxygen inlet lance. The flame temperature is controlled by varying the oxygen flow while always using excess hydrogen.…”
Section: Methodsmentioning
confidence: 99%
“…5 The technique presented here is used in conjunction with the flame-based high-temperature reducing jet aerosol reactor developed by Scharmach et al shown schematically in Figure 1. 6 Carbon coated nanoparticles have been previously reported by several groups, but in contrast to this contribution, the carbon coating in those cases was not intended to encapsulate multiple particles or improve particle collection and handling. Luechinger et al synthesized copper nanoparticles using a bottom up approach with in situ formation of protective shells of graphene to produce air-stable and chemically inert material.…”
Section: Introductionmentioning
confidence: 95%
“…A dosage of excess of hydrogen should be avoided. Reduction processes could change the composition of ZnO particles as seen in experiments with the formation of copper particles by Scharmach et al (2010). To protect the flame cone against additional oxygen from ambient air or atomizing gas, we used argon as the sheath gas (optimum flow rate was 4 L/min) in combination with nitrogen as the atomizing gas (pressure 0.30 bar).…”
Section: Trace Gas Analysesmentioning
confidence: 99%